ANALISIS PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2022-2024 - Ramdhan , M.Rizki; Wijaya, Rico; Hernando, Riski (Jurusan Akuntansi FEB Universitas Jambi, 2026)
This study aims to examine the effect of financial performance on stock prices, with firm size as a moderating variable, among companies in the food and beverage subsector listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024. Financial performance in this study is measured using several financial ratios, namely Return on Assets (ROA), Current Ratio (CR), Debt-to-Equity Ratio (DER), Total Asset Turnover (TATO), and firm size is measured by Total Assets. This study employs a quantitative approach using secondary data obtained from companies’ financial statements. The sampling technique used purposive sampling, and data analysis was conducted using the Partial Least Squares-based Structural Equation Modeling (SEM-PLS) method with WarpPLS 8.0 software. The results of this study indicate that ROA and CR have a positive and significant effect, while DER and TATO have a negative and significant effect on stock prices. Company size was found to negatively and significantly moderate the effect of ROA on stock price and to positively and significantly moderate the effect of DER. However, company size did not moderate the effects of CR and TATO on stock price.